2003
DOI: 10.1081/ncn-120022731
|View full text |Cite
|
Sign up to set email alerts
|

Nuclease Stability of LNA Oligonucleotides and LNA-DNA Chimeras

Abstract: The stabilizing properties of LNA and alpha-L-LNA oligonucleotides against endo- and 3'-exonucleases have been evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 4 publications
0
38
0
Order By: Relevance
“…This bridge results in a locked 3'-endo conformation, which reduces the flexibility of the ribose, and allows for stable triplex formation [69][70][71][72]. LNA modifications within a TFO can increase the binding affinity to the target duplex DNA, and can increase resistance to digestion by nucleases [73]. Beane et al, have demonstrated that LNAs can recognize chromosomal target sequences and efficiently block endogenous expression of the progesterone and androgen receptors [74].…”
Section: Chemical Modifications Of Tfosmentioning
confidence: 99%
“…This bridge results in a locked 3'-endo conformation, which reduces the flexibility of the ribose, and allows for stable triplex formation [69][70][71][72]. LNA modifications within a TFO can increase the binding affinity to the target duplex DNA, and can increase resistance to digestion by nucleases [73]. Beane et al, have demonstrated that LNAs can recognize chromosomal target sequences and efficiently block endogenous expression of the progesterone and androgen receptors [74].…”
Section: Chemical Modifications Of Tfosmentioning
confidence: 99%
“…Therefore, in this study, we used third-generation LNA oligonucleotide technology, where 6 of the 16 complementary oligonucleotide residues are composed of ribose sugars that are locked in a conformation that provides much higher binding affinity to the complementary mRNA than conventional DNA and 2 0 -MOE (2 0 -O-methoxyethyl)-based oligonucleotides (10). Such LNA oligonucleotides have low single-digit nanomolar or high picomolar IC 50 values for mRNA downmodulation that have been achieved in cell culture for LNA-ASOs against AR as well as HIF-1a (13) and survivin (14,23) when used with transfection reagents.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, LNA-ASOs have shown very high binding affinity to mRNA, excellent potency for target mRNA downmodulation, improved resistance to nuclease digestion, and excellent stability in plasma and tissues in preclinical studies (10). These features allow LNAASOs simplistically prepared in saline to be highly effective in vitro and in vivo (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Complete stability against the 3 0 -exonuclease snake venom phosphodiesterase (SVPD) was reported for a fully modified LNA [10] while a significant increase in 3 0 -exonucleolytic stability was observed by blocking the 3 0 -end with two LNA monomers. In a study of oligonucleotide stability in serum, LNA mixmers were found to be very stable and LNA/DNA/ LNA gapmers (see section below for definition of gapmers) to be significantly more stable than DNA alone [11].…”
Section: Susceptibility Of Lna To Nucleasesmentioning
confidence: 99%